Elegies for Sons in the poetry of Al-Utbi Al-Qurashi - Kareem Abd, Huda ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2026)
The current study addresses the phenomenon of children’s eulogy in the poetry of Al-Utbi Al-Qurashi, who is one of the poets who mourned their children and expressed their deep sorrow over the loss of their beloved ones. The poet excelled in this kind of poetry. He having lost six of his children. His poems embodied the tragedy of loss, laden with sadness and grief. The poet expressed his inner devastation at the loss of all his children. The loss of a son is unlike any other loss. For this reason, his poems became a distinct artistic and humanistic model for expressing loss. Grief appeared as a dominant value in the texts, along with a tragic depiction of the loss of a son. Al-Utbi resorted to simple words and sincere expressions in embodying scenes of loss and grief. His verses were an extension of sincere humanistic emotion, avoiding affectation and complexity. He focused in his poetry on the pain of a father in losing his son. It is an extraordinary pain because it is irreplaceable and unforgettable. DOI: https://doi.org/10.54633/2333-024-057-018